2010
DOI: 10.1007/s11605-009-1123-0
|View full text |Cite
|
Sign up to set email alerts
|

Periampullary and Duodenal Neoplasms in Neurofibromatosis Type 1: Two Cases and an Updated 20-Year Review of the Literature Yielding 76 Cases

Abstract: These results underscore the importance of a thorough evaluation for tumors in NF1 patients with gastrointestinal symptoms, as well as subsequent surgical management when findings suggest a tumor in the periampullary region, as resection remains the mainstay of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
1
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 66 publications
0
65
1
15
Order By: Relevance
“…To our knowledge, only 13 cases with the triad of GIST, dSOM and NF-1 have previously been reported [28,29,30,31,32,33,34,35,36,37,38,39,40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 13 cases with the triad of GIST, dSOM and NF-1 have previously been reported [28,29,30,31,32,33,34,35,36,37,38,39,40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…café-au-lait spots, axillary and inguinal freckling, iris hematomas and optic gliomas (Basile et al 2010, Relles et al 2010, Pasmant et al 2012. The prevalence of NF1 is about 1 in 3000 individuals.…”
Section: :9mentioning
confidence: 99%
“…The prevalence of NF1 is about 1 in 3000 individuals. Approximately 40% of periampullary duodenal somatostatinomas are associated with NF1 (Relles et al 2010). PCCs and NET in other locations, including the pancreas can also develop (Perren et al 2006).…”
Section: :9mentioning
confidence: 99%
“…In their review, they observed that 60 % of the tumors were located in the duodenum, 31 % were of the ampulla of Vater, 5 % in pancreas, and 4 % in the bile duct or gallbladder. NETs represented 47 % of all periampullary tumors (40 % somatostinoma, 6 % carcinoid, and 1 % malignant) and 34 % were GISTs [9]. Although somatostinomas are the most frequent NETs in NF1, they rarely develop somatostatinoma syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…They appear in 5-25 % of NF1 patients, are multiple in 60 % of cases, and appear in the duodenum in 20-30 % of patients. Indolent in most cases, severe gastrointestinal bleeding is a common complication [9]. However, without histopathological examination, definitive diagnosis is challenging.…”
Section: Discussionmentioning
confidence: 99%